Respuesta :
we have
[tex] 2x^{2} + 5x + 3 [/tex]
equate the expression to zero
[tex] 2x^{2} + 5x + 3 =0 [/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex] 2x^{2} + 5x =-3 [/tex]
Factor the leading coefficient
[tex] 2(x^{2} + 2.5x) =-3 [/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex] 2(x^{2} + 2.5x+1.5625) =-3+3.125 [/tex]
[tex] 2(x^{2} + 2.5x+1.5625) =0.125 [/tex]
Rewrite as perfect squares
[tex] 2(x+1.25)^{2} =0.125 [/tex]
[tex] (x+1.25)^{2} =0.0625 [/tex]
[tex] (x+1.25) =(+/-)\sqrt{0.0625} \\ x1=-1.25+\sqrt{0.0625}\\ x2=-1.25-\sqrt{0.0625} [/tex]
Simplify
[tex] x1=-1.25+\sqrt{0.0625}\\ x1=-1.25+0.25\\ x1=-1 [/tex]
[tex] x2=-1.25-\sqrt{0.0625}\\ x2=-1.25-0.25\\ x2=-1.50 [/tex]
[tex] 2x^{2} + 5x + 3=2(x+1.5)(x+1)\\ =(2x+3)(x+1) [/tex]
therefore
the answer is
the missing term in the factorization is [tex] 1 [/tex]
The missing term in the factorization of the given quadratic expression (2x² + 5x + 3) is determined as (x + 1).
Factorization of the quadratic equation
The given quadratic equation can be factorized as follows;
2x² + 5x + 3
2x² + 2x + 3x + 3 (5x = 2x + 3x)
factorize similar terms together
2x(x + 1) + 3(x + 1)
The factorized form = (2x + 3)(x + 1)
Thus, the missing term in the factorization of the given quadratic expression (2x² + 5x + 3) is determined as (x + 1).
Learn more about factorization here: https://brainly.com/question/25829061